Perancangan Sistem Informasi Buku Tamu Pada Instansi Badan Penelitian Dan Pengembangan Daerah Provinsi Sumatera Selatan - Selvi, Dwi; Hidayanti, Indah (MDP Student Conference, 2024)
The Regional Research and Development Agency Office of South Sumatra Province, known as balitbangda, is an agency at the provincial level which is responsible for carrying out tasks in the field of regional research and development. The Regional Research and Development Agency (Balitbangda) is a supporting element led by an Agency Head and is under and responsible to the Governor through the Regional Secretariat. The South Sumatra Province Regional Research and Development Agency as a regional apparatus organization which is a supporting element, assists the Governor in administering the Provincial government in the fields of research, development, engineering, utilization and innovation of science and technology as stipulated in the South Sumatra Governor's regulation Number 51 of 2020 concerning organizational structure, description of the duties and functions of the South Sumatra Province Regional Research and Development Agency. In managing the guest book at the Balitbangda of South Sumatra Province, it still uses manual methods so that delays and errors often occur in registering guests. The method used is the Waterfall method, the stages of Waterfall is Analysis, Design, Implementation and Testing. The data collection methods are through observation, documentation and interviews. The results of this research are to make it easier for employees to register guests at the South Sumatra Province Regional Research and Development Agency.